Decentralization Process in Portugal: impact in the health care system. (30th September 2020) - Sequeira, R; Quinaz Romana, G; Campos Fernandes, A; Pinho, M; Freire Rodrigues, E; Isoppo, C; Sousa, P
Abstract: Problem: Different countries have incorporated models of decentralization in their health reforms to achieve efficiency, by increasing the training of local governments, responsibility and gains in areas such as quality, costs and equity. In Portugal, the 21st government program established the autonomy of local authorities and the democratic decentralization of public administration. Accordingly, a decentralization law was approved and local governments have now a crucial role on health policies. Description of the Problem: For this framework, a situational diagnosis and an intersectoral approach to policies are needed. This is an observational, analytical and cross-sectional study developed at council level in two Portuguese municipalities. This study aims to: Adjust responses to health needs at the local level; Set priorities by taking into account installed capacity and responses to populations; Promote the articulation between entities; Strengthen the focus on health promotion and healthy lifestyles; Strengthen health interventions in educational communities; Promote the creation of programs at local level, in conjunction with the national level, to reduce inequalities. Results: The preliminary results in health, social and economic indicators show that this framework, while taking in consideration population characteristics, allows the development of local strategies regarding health services coverage, health services type and medication. At council level, the preliminary results also show a lack of data on healthy lifestyles and social indicators. Lessons: The implementation of a decentralization process involves a broad range of requirements such as a situational diagnosis, strategies development and a periodic update of quality life and health indicators. Those are needed to assess council level priorities, which allow the development of public policies and interventions, in line with population characteristics, to tackle health inequalities and inequities. Key messages: Performance improvement of health system is linked to the implementation of local citizen centred policies. These are actions which promote quality of life through health-friendly ecosystems. The local health intervention has contributed to promote inequalities reduction, increasing equity and dynamize new frameworks of organization with individual and community participation.